Genetic improvement and related activities. Improvement of individual characters. N-fixation - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
In the 1986 breeding program for enhanced N fixation, emphasis was placed on small seeded indeterminate beans; however, at the beginning of 1986 it was decided that some priority should be given to materials for Africa, including larger seeded determinate and indeterminate bush types. In Popayan, Colombia, some lines such as Canadian Wonder, Catrachita, and RIZ 30 demonstrated good early nodulation, but by mid-flowering the nodules were already starting to senesce. In collaboration with Rothamsted Exptl. Station, United Kingdom, investigations into obtaining nonnodulating and supernodulating bean lines (lines which continue to nodulate in the presence of nitrate and which nodulate more than usual under all conditions) by mutation were carried out. Nodule mass is 1 component which has been identified in beans as contributing to improved fixation. Expt. carried out under field and glasshouse conditions to measure N fixation of different bean genotypes showed similar differences in N fixation. In general, the RIZ lines and A 268 fixed more N than the BAT lines. Data on differences between Rhizobium strains in tolerance and growth at low and high temp. are presented. (CIAT)